MESA SA KWARTO: SOUTHEAST ASIAN EXHIBITION ON A ‘TINY DESK’ HELD IN A LIVE ZOOM GALLERY - Agustin, Kristian Jeff Cortez (Animus. Revista Interamericana de Comunicação Midiática, 2021)
In 2020, workers had been deprived of access to their desk jobs as mass lockdowns shuttered offices. Videoconferencing arguably offered makeshift, temporary solutions across industries. Curator-researcher Agustin challenged the now ubiquitous Zoom-based communication by way of producing an online exhibition from his very own lockdown workplace. Mesa Sa Kwarto, thus, expanded the now ubiquitous Zoom gallery view into a makeshift exhibition space, where the desk (mesa) in the room (kwarto) balances between the material and virtual, offline and online, work and life. The effect can be likened to a home-made rendering of augmented reality. This study offers a critical reflection on how a makeshift physical-yetonline exhibition space can be considered as a potential form of counter-visuality to the alienating and homogenising tendencies of COVID-19 lockdowns, Zoom and social media.